Chitosan/glycosaminoglycan scaffolds for skin reparation. (15th September 2019) - Sandri, Giuseppina; Rossi, Silvia; Bonferoni, Maria Cristina; Miele, Dalila; Faccendini, Angela; Del Favero, Elena; Di Cola, Emanuela; Icaro Cornaglia, Antonia; Boselli, Cinzia; Luxbacher, Thomas; Malavasi, Lorenzo; Cantu', Laura; et al.
Graphical abstract: Highlights: Electrospun chitosan/glycosaminoglycan scaffolds for skin reparation were developed. The scaffolds were insoluble in aqueous fluids after crosslinking by heating. Chondroitin sulfate renders the scaffold best suited to heal lesions in murine model. Chondroitin sulfate provides system flexibility for optimal preclinical performance. Abstract: Burns and chronic wounds, often related to chronic diseases (as diabetes and cancer), are challenging lesions, difficult to heal. The prompt and full reconstitution of a functional skin is at the basis of the development of biopolymer-based scaffolds, representing a 3D substrate mimicking the dermal extracellular matrix. Aim of the work was to develop scaffolds intended for skin regeneration, according to: fabrication by electrospinning from aqueous polysaccharide solutions; prompt and easy treatment to obtain scaffolds insoluble in aqueous fluids; best performance in supporting wound healing. Three formulations were tested, based on chitosan (CH) and pullulan (P), associated with glycosaminoglycans (chondroitin sulfate - CS or hyaluronic acid – HA). A multidisciplinary approach has been used: chemico-physical characterization and preclinical evaluation allowed to obtain integrated information. This supports that CS gives distinctive properties and optimal features to the scaffold structure for promoting cell proliferation leading tissue reparation towards a complete skin restore.